155k views
3 votes
Simplify n^6 * n^5 / n^4 * n^3 /n^2 * nThere is a picture too.

Simplify n^6 * n^5 / n^4 * n^3 /n^2 * nThere is a picture too.-example-1
User Abalakin
by
7.6k points

1 Answer

5 votes

Given the following expression:


n^6\cdot n^5(\cdot)/(\cdot)n^4\cdot n^3(\cdot)/(\cdot)n^2\cdot n

to simplify, we have to operate from left to right, then, we get the following:


\begin{gathered} n^6\cdot n^5(\cdot)/(\cdot)n^4\cdot n^3(\cdot)/(\cdot)n^2\cdot n=n^(11)(\cdot)/(\cdot)n^4\cdot n^3(\cdot)/(\cdot)n^2\cdot n^{} \\ =n^7\cdot n^3(\cdot)/(\cdot)n^2\cdot n=n^(10)(\cdot)/(\cdot)n^2\cdot n=n^8\cdot n=n^9 \end{gathered}

therefore, the simplified expression is n^9

User Jagmohan
by
7.0k points